2010
DOI: 10.1002/prca.200900171
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic biomarkers for overall and progression‐free survival in ovarian cancer patients

Abstract: We found an index with three proteomic biomarkers (xb-pro) to be of independent prognostic value for overall survival and an index with two proteomic biomarkers (xb-pfs) with evidence of independent prognostic value for progression-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Serum CA125 has been used extensively in advanced epithelial ovarian cancer diagnosis, with 80% success. However increased CA125 was observed in only 50-60% of stage I patients [3,4], leading to 10% success with CA125 alone or 20% when combined with ultrasonic examination. This emphasized the importance of finding a highly sensitive and specific biomarker for early diagnosis of ovarian cancer [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Serum CA125 has been used extensively in advanced epithelial ovarian cancer diagnosis, with 80% success. However increased CA125 was observed in only 50-60% of stage I patients [3,4], leading to 10% success with CA125 alone or 20% when combined with ultrasonic examination. This emphasized the importance of finding a highly sensitive and specific biomarker for early diagnosis of ovarian cancer [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…ROMA combines two proteins, carbohydrate antigen 125 (CA125) and human epididymis protein 4 (HE4) that were identified as over expressed mRNA in ovarian cancer (Hellstrom et al, 2003). And OVA1 includes five proteins (CA125, b2-microglobulin, transferrin, apolipoprotein A1, transthyretin), four of which were identified using the Surface-Enhanced Laser Desorption/ Ionization-Time Of Flight (SELDI-TOF) platform (Høgdall et al, 2010). It is important to underline that all three biomarkers mentioned use a panel of multiple proteins to improve prediction performance.…”
Section: Biomarkersmentioning
confidence: 99%
“…Despite disease heterogeneity and interexperimental reproducibility (61)(62)(63), surface-enhanced laser desorption ionization time-of-flight mass spectrometry (SELDI-TOF MS) is a useful proteomic method of discovering differentially expressed biomarkers (i.e., m/z peaks) that may be used to biochemically classify ovarian tumors (64)(65)(66), and to develop cancer prevention, screening, and treatment strategies (67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80). However, only a few studies have identified the underlying proteins of the biomarker peaks seen in SELDI-TOF MS spectra (69,72,79,(81)(82)(83)(84)(85), which typically requires an integrated, labor-intensive chromatographic, electrophoretic, and mass spectrometric approach.…”
Section: Introductionmentioning
confidence: 99%